Answer:
Explanation:
3
2
−
2
3
y+
3
1
y+4=0
Combine −
2
3
y and
3
1
y to get −
6
7
y.
3
2
−
6
7
y+4=0
Convert 4 to fraction
3
12
.
3
2
−
6
7
y+
3
12
=0
Since
3
2
and
3
12
have the same denominator, add them by adding their numerators.
3
2+12
−
6
7
y=0
Add 2 and 12 to get 14.
3
14
−
6
7
y=0
Subtract
3
14
from both sides. Anything subtracted from zero gives its negation.
−
6
7
y=−
3
14
Multiply both sides by −
7
6
, the reciprocal of −
6
7
.
y=−
3
14
(−
7
6
)
Multiply −
3
14
times −
7
6
by multiplying numerator times numerator and denominator times denominator.
y=
3×7
−14(−6)
Do the multiplications in the fraction
3×7
−14(−6)
.
y=
21
84
Divide 84 by 21 to get 4.
y=4